The Western Welfare State in The 1990s: Toward a New Model of Antipoverty Policy for Families with Children - Sheldon H. Danziger; Timothy Michael Smeeding; Lee Rainwater (Luxembourg Income Study (LIS), 1995)
This paper is motivated by the fact that even though most advanced economies have experienced similar changes in family structure and in the structure of their labor markets during the past two decades, their child poverty rates vary dramatically, from less than 3 percent to more than 20 percent. This paper describes a series of family, labor market and public policy changes that have affected children in all advanced economies. The authors find that differences in public policies account for a significant portion of the variation in poverty rates and find that the differences reflect differing social and political values and choices, not technical economic constraints. The authors conclude that there is enough flexibility in the choices that can be made so that all modern advanced countries and eventually the transition economies of Eastern Europe can achieve both a dynamic, growing economy and a low child poverty rate.
Keywords: 330; Kinder; Jugendliche; Armutsbekämpfung; Familienpolitik; OECD-Staaten